Weight for gestational age and metabolically healthy obesity in adults from the Haguenau cohort. Issue 8 (31st August 2016) - Matta, Joane; Carette, Claire; Levy Marchal, Claire; Bertrand, Julien; Pétéra, Mélanie; Zins, Marie; Pujos-Guillot, Estelle; Comte, Blandine; Czernichow, Sébastien
Abstract : Background: An obesity subphenotype, named 'metabolically healthy obese' (MHO) has been recently defined to characterise a subgroup of obese individuals with less risk for cardiometabolic abnormalities. To date no data are available on participants born with small weight for gestational age (SGA) and the risk of metabolically unhealthy obesity (MUHO). Objective: Assess the risk of MUHO in SGA versus appropriate for gestational age (AGA) adult participants. Methods: 129 young obese individuals (body mass index ≥30 kg/m²) from data of an 8-year follow-up Haguenau cohort (France), were identified out of 1308 participants and were divided into 2 groups: SGA (n=72) and AGA (n=57). Metabolic characteristics were analysed and compared using unpaired t-test. The HOMA-IR index was determined for the population and divided into quartiles. Obese participants within the first 3 quartiles were considered as MHO and those in the fourth quartile as MUHO. Relative risks (RRs) and 95% CI for being MUHO in SGA versus AGA participants were computed. Results: The SGA-obese group had a higher risk of MUHO versus the AGA-obese group: RR=1.27 (95% CI 1.10 to 1.6) independently of age and sex. Conclusions: In case of obesity, SGA might confer a higher risk of MUHO compared with AGA.